2009
DOI: 10.1080/13697130802638458
|View full text |Cite
|
Sign up to set email alerts
|

Postmenopausal hormone therapy with estradiol and norethisterone acetate and mammographic density: findings from a cross-sectional study among Norwegian women

Abstract: Our study suggests that the effect of E2/NETA regimens on mammographic density could be at least as detrimental to the breast tissue as several other estrogen + progestin regimens. Our results suggest that both low- and high-dose E2/NETA influence mammographic density, but there were some indications in our analyses that the effect of low-dose E2/NETA could be slightly lower than that of the older high-dose regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…It has been consistently shown that combined estrogen-progestogen therapy (EPT) increases mammographic density [7][8][9][10][11][12][13][14][15][16][17][18]. However, certain aspects of this association need to be further clarified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been consistently shown that combined estrogen-progestogen therapy (EPT) increases mammographic density [7][8][9][10][11][12][13][14][15][16][17][18]. However, certain aspects of this association need to be further clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is not clear whether different types of EPT have different effects on mammographic density. For example, norethisterone acetate (NETA) regimens have been shown to be associated with a higher risk of breast cancer than other types of EPT [19], but only a limited number of studies have examined whether this type of EPT affects mammographic density differently than other types [7,15]. Furthermore, few studies have investigated mammographic density in relation to duration of hormone therapy (HT) use, or the time since stopping HT, and the results have been inconclusive [7,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Such effects have been monitored by sequential mammograms for the risk factors age, menopause, HRT and even for anti-hormone treatment (Byrne et al, 1995;Atkinson et al, 1999;Brisson et al, 2000;Vachon et al, 2000;Rutter et al, 2001;Greendale et al, 2003;Cuzick et al, 2004;Warren, 2004;Maskarinec et al, 2006;Boyd et al, 2006a;Kerlikowske et al, 2007;Stuedal et al, 2009). Concerning age, the average percentage of density in women in the National Breast Screening Study (Boyd et al, 2002;Russo et al, 2006) differed by 20% between the ages 40-44 and 55-59 years, compared with an 8% reduction in percentage of MD observed over 5 years in individuals who went through menopause, compared with 2% in women of the same age who did not experience menopause.…”
Section: Introductionmentioning
confidence: 99%
“…The authors suggested that these findings might have been explained by the differentiation of breast cells promoted by melatonin (42). However, if melatonin is to exert the antiestrogenic action, one would have expected a decrease, not an increase in mammographic density (55)(56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%